Components of Contextual Teaching and Learning as The Basis for Developing a Character Education Model - Everhard Markiano Solissa; Sofyan Mustoip; Marlina Marlina; Sri Supiah Cahyati; Asdiana Asdiana (Universitas of Muhammadiyah Makassar, 2023)
Implementation of character education in Indonesia still leaves its own problems, such as the practice of character education that is carried out does not emphasize the process of involving students to find material, character education is not directed at encouraging students to find relationships between learning experiences at school and real life education. Characteristics that have been held so far have not been able to encourage students to be able to apply and apply them in real life. The purpose of this research was to explain the Components of Contextual Teaching and Learning as the Basis for the Developing A Character Education Model. The research method used in this research was qualitative. Data collection techniques using documentation and literature. Data collection techniques for literature studies are carried out by collecting books and articles from scientific journals that are relevant to research problems. The data obtained were then analyzed descriptively qualitatively. The results of this research indicated that the components of contextual teaching and learning as the basis for developing a character education model, namely (a) constructivism, (b) inquiry, (c) asking (d) learning communities, (e) modeling, (f) reflection, (g) actual assessment. Thus it can be concluded that the Components of Contextual Teaching and learning can be used as the basis for developing a character education model.